Preoperative serum inflammatory markers in the prognostic assessment of hepatocellular carcinoma resection in stages I/II - Liu, Fan; Xiang, Yuan; Xu, Hao; Xu, Xiaoxue (Frontiers in Molecular Biosciences, 2025)
BackgroundHepatocellular carcinoma (HCC) remains a global health challenge, with early-stage resection offering the best chance for improved outcomes. However, limitations of the TNM staging system highlight the need for additional prognostic tools. This study evaluates the prognostic value of preoperative serum inflammatory markers in patients with stage I/II HCC undergoing surgical resection.MethodsA retrospective cohort study was conducted on 410 HCC patients (stage I/II) who underwent surgical resection at the Affiliated Hospital of North Sichuan Medical College between November 2011 and March 2020. Clinical and serological data, including neutrophil-to-lymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR), and platelet-to-neutrophil ratio (PNR), were analyzed. Prognostic factors for overall survival (OS) were identified through univariate and multivariate Cox regression analyses. A nomogram was developed to predict 1-year, 3-year, and 5-year OS, with its performance assessed using ROC curves, calibration plots, and decision curve analysis (DCA). Kaplan-Meier survival curves were used to compare risk groups, and the model’s predictive efficacy was evaluated against the AJCC 8th Edition TNM staging system.ResultsMultivariate Cox regression identified NLR, PLR, ALBI score, AFP levels, and HBeAg status as independent prognostic factors for OS. The nomogram demonstrated superior discriminatory power (AUC: 0.78, 0.74, and 0.71 for 1-, 3-, and 5-year OS, respectively) compared to TNM staging. Kaplan-Meier analysis revealed significantly worse OS in the high-risk group (log-rank p < 0.001). The nomogram outperformed the AJCC TNM system in both discrimination and clinical utility, as validated by decision curve analysis and the Integrated Discrimination Improvement Index.ConclusionPreoperative serum inflammatory markers, when integrated with traditional TNM staging, significantly improve prognostic accuracy for stage I/II HCC patients undergoing surgical resection. The developed nomogram provides a practical tool for individualized risk stratification and may guide postoperative management to improve patient outcomes.